White matter correlates of neuropsychological function in young adult methamphetamine users - Freeman, Carla Patricia (Division of Neuropsychiatry, 2017)
Background: Methamphetamine (MA) abuse is a global health concern due to widespread use and harmful effects, which includes neurotoxicity. This study aimed to describe neurocognitive deficits associated with MA dependence in young adults and to explore whether these deficits correlate with white matter (WM) microstructural abnormalities using diffusion tensor imaging (DTI). Methods: Twenty-one MA dependent individuals recently enrolled in an outpatient rehabilitation program and nineteen healthy controls participated in the study. Each participant completed a neuropsychological evaluation and underwent diffusion tensor imaging within one week of testing. Average whole-brain fractional anisotropy (FA) and mean diffusion (MD) measures derived from DTI data were compared between groups. Group differences in performance within specific neurocognitive domains and in a composite global neurocognitive score (GNS) were tested using non-parametric univariate statistics and within a linear regression framework, adjusting for age and gender. Correlation analyses were conducted to test associations between the neuropsychological data and selected frontal white matter (WM) tracts, including the genu and body of the corpus callosum (CC); right and left cingulum bundle (CB); right and left uncinate fasciculus (UF); right and left anterior corona radiata (CR) and the right and left superior longitudinal fasciculus (SLF). Results: No significant between-group differences were detected for performance in any of the neuropsychological domains assessed. No relationship between FA or MD and the GNS was demonstrated in the tracts of interest. After adjusting for age and gender, significant group differences in FA and MD were detected across several regions of interest (ROI), however, these did not survive corrections for multiple comparisons. Conclusion: Cognitive performance and white matter integrity did not differ between young MA dependent subjects and healthy controls. Whatever differences that were found in white matter did not survive correction for multiple comparisons. These findings may reflect one or more of several possibilities: that brain function and structure is relatively preserved in younger individuals; or that differences were too small to be detected in this sample. Further studies should explore the effects of aging, poly-substance abuse and HIV coinfection on neurocognitive functioning and structural brain integrity in methamphetamine users.